Pregnancy-Associated Plasma Protein-A: Its Significance as a Single Biomarker for Adverse Obstetric Outcomes - Madhusudan Dey; Priyanshi Choudhury; Sunil Chawla; Pranjali Dhume; Suyash Goel; Ankur Shah; Mounica Gowda KN (Gynecology Obstetrics & Reproductive Medicine)
OBJECTIVES: Low levels of pregnancy-associated plasma protein-A in pregnant women linked to unhealthy placentation and a spectrum of maternal and fetal complications. Its assessment as a single biomarker has the potential to identify high-risk pregnancies. This prospective observational study was conducted to find a correlation between low pregnancy-associated plasma protein-A levels in the first trimester of pregnancy with various obstetric outcomes to establish if it can be used as a single biomarker for counseling couples.